Resources on the Stage: A Firm Level Analysis of the ICT Adoption in Turkey - Derya Findik; Aysit Tansel (Institute for the Study of Labor (IZA), 2015)
This study examines the impact of firm resources on ICT adoption by the Turkish business enterprises using firm level data. ICT adoption is measured at three levels: The first level is technology ownership. The second level is the presence of enterprise resource planning (ERP) and customer resource management (CRM), and the third level is the use of narrowband and broadband technologies. The effects of the three main features of each technology level, which are complementarity, specificity, and the complexity, are analyzed by using firm level data in Turkey. This study has three main conclusions. As for the complementarity, firm's resources play an important role in the adoption of technology while advancing from single technology to the multiple ones. Further, in the use of specific technologies such as ERP and CRM, firm resources generate differential effects between those technologies. Finally, the use of simple technologies does not require the same amount of firm resources as complex technologies.
Keywords: D22; D24; O30; O47; 330; specificity; complementarity; ICT; adoption; complexity